La industria lítica del núcleo urbano Maya De La Blanca, Petén, Guatemala : tecnología y tipología - Torres Marzo, Ricardo, 1980- (Paris monographs in American archaeology ;, 2021)
The ancient Maya used mainly stone tools, made of either ground stone and chipped stone, to achieve their extraordinary development. This book presents the techno-typological analysis of lithic materials from La Blanca, located in the heart of the Southern Lowlands, which was mainly inhabited during the Late Classic and Terminal Classic periods.